A partial least squares structural equation modeling (PLS-SEM) of energy management critical success factors to sustainable university in Malaysia - Abdullah Saleh, Alia; Hashim, Hasnan; Awang, Mariah; Ahmad Zawawi, Zuraihana; Aswad, Mohd Khazli; Sudirman, Mohd Dzulkarnaen (Science & Engineering Research Support Society (SERSC), 2020)
This paper analyzes the critical success factors (CSFs) in energy management (EM) for the implementation of Sustainable University (SU) Key Performance Indicators (KPIs) at Malaysian research universities. Through a thorough review of the literature, CSFs related to EM were established, which were then contextually tailored through a pilot study and presented as a hypothesized template. Primary data was collected to 300 academic and non-academic staff of five research universities in Malaysia through questionnaire surveys. Modeling of the structural formula of partial least squares (PLS-SEM) was used to statistically verify the final version of the EM CSFs to achieve SU. This paper fills the knowledge gap by concentrating on the quantified contribution to the adoption of SU in Malaysia by the most significant EM CSFs. Findings from this paper have confirmed the hypotheses that four EM CSFs have a significant relationship to KPIs namely, top management support, understanding, strong stakeholder relationships, and risk management which ultimately lead to successful adoption of EM in achieving SU. It is hoped that the findings will provide guidelines for the Malaysian Higher Education Ministry to be more effective in achieving sustainability for all universities.